The prevalence of overweight and obesity in adolescents from 1988 to 2014: results from the HBSC Portuguese survey - Marques, Adilson (2021)
ABSTRACT - Objective: Using a national representative sample of Portuguese adolescents, this study aimed to report the prevalence of overweight and obesity over 16 years, from 1998 to 2014. Methods: The total sample comprised 26,479 adolescents (12,711 boys and 13,768 girls) aged 11–16 years (mean age ± SD = 13.5 ± 1.7) from the Health Behaviour in Schoolaged Children (HBSC) Portuguese survey cohorts from 1998 (n = 5,999), 2002 (n = 5,454), 2006 (n = 4,430), 2010 (n = 4,702), and 2014 (n = 5,894). Weight and height were selfreported. The prevalence of overweight and obesity was calculated along with a 95% confidence interval (CI). Results: The highest prevalence of overweight and obesity was achieved in 2010 (20.5%; 95% CI: 19.5, 21.9) and the lowest in 1998 (17.8%; 95% CI: 16.8, 18.8). The results of trend tests between 1998 and 2014 show that there was no significant change in overweight and obesity prevalence. Although the prevalence of obesity increased from 1998 to 2014 for the entire sample (0.8%; 95% CI: –5.5, 7.0), for boys (1.1%; 95% CI: –4.1, 6.3), and girls (0.5%; 95% CI: –4.5, 5.4), there were no significant changes in obesity prevalence. Conclusion: The prevalence of overweight and obesity in Portuguese adolescents was around 20% between 1998 and 2014. The extent of overweight and obesity seems to have stabilized over time.